2018
DOI: 10.3390/cancers10100366
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Tumor-Associated Macrophages in Ovarian Cancer as Targets for Therapy

Abstract: Ovarian cancer, a rare but fatal disease, has been a challenging area in the field of gynecological cancer. Ovarian cancer is characterized by peritoneal metastasis, which is facilitated by a cross-talk between tumor cells and other cells in the tumor microenvironment (TME). In epithelial ovarian cancer, tumor-associated macrophages (TAMs) constitute over 50% of cells in the peritoneal TME and malignant ascites, and are potential targets for therapy. Here, we review the bipolar nature of TAMs and the evolving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 76 publications
5
68
0
Order By: Relevance
“…Ascite, which is a hallmark of OC, contains a large number of components of unique peritoneal TME, including tumor spheroids and immune cells, such as TAMs and T cells (201,202). Experimental mouse models have demonstrated that TAMs constitute a major cell fraction in ascites that support the survival of cancer cells and promote cancer progression, chemoresistance, and immunosuppression (202,204,(221)(222)(223).…”
Section: Ascitic Tams In Metastasis Of Ovarian Cancermentioning
confidence: 99%
“…Ascite, which is a hallmark of OC, contains a large number of components of unique peritoneal TME, including tumor spheroids and immune cells, such as TAMs and T cells (201,202). Experimental mouse models have demonstrated that TAMs constitute a major cell fraction in ascites that support the survival of cancer cells and promote cancer progression, chemoresistance, and immunosuppression (202,204,(221)(222)(223).…”
Section: Ascitic Tams In Metastasis Of Ovarian Cancermentioning
confidence: 99%
“…110 Metastatic ovarian cancer is characterized by ascites and tumor implants in the peritoneal cavity. 111 Unfortunately, results of several single-agent CBT clinical trials in ovarian cancer are discouraging, with objective response rates of 6%-15%. 7 As a result, there are no FDA-approved checkpoint inhibitors for ovarian cancer beyond the use of anti-PD-1 (pembrolizumab) for microsatellite instability-high tumors.…”
Section: Myeloid Apc In Cbt-resistant Carcinomas Invasive Breast Carcmentioning
confidence: 99%
“…128 They are highly plastic and depending on the cytokines and growth factors present in the TME, they can be skewed toward an inflammatory M1-like state or an immunosuppressive M2-like state. 111 Studies have shown that high amounts of CSF1 secreted by ovarian cancer cells can cause PM to differentiate into CD206 + M2 TAM. 129 The resulting increase in the M2/M1 phenotype ratio of TAM has been shown to correlate with decreased survival in patients with ovarian cancer.…”
Section: Myeloid Apc In Cbt-resistant Carcinomas Invasive Breast Carcmentioning
confidence: 99%
“…For example, miR-21-3p, miR-125b-5p, and miR-181d-5p are highly expressed in exosomes derived from EOC, which are involved in M2 polarization of macrophages in hypoxic conditions [30]. Macrophages modified by exosomes promote the proliferation and migration of EOC [31]. The expression and function of exosomal miR-214-3p identified in this study suggest that miR-214-3p may contribute to the oncogenic effects of exosomes by affecting other cell types in the tumor microenvironment of EOC.…”
Section: Discussionmentioning
confidence: 99%